THE EFFECT OF FIRM SPECIFIC AND MACROECONOMIC FACTORS ON CAPITAL STRUCTURE OF FOOD AND BEVERAGE INDUSTRY LISTED IN COLOMBO STOCK EXCHANGE - Sooriyakumar, K.; Pirahalathan, B.; Sathiyamoorthy, S. (My University, 2016)
This paper studies the effects of firm specific and macroeconomic factors on capital structure of food and beverage industry listed in Colombo Stock Exchange (CSE). For this study, fourteen companies were selected from the food and beverage companies listed in the CSE. Data for firm specific variables and macroeconomic variables from 2009 to 2015 were collected from CSE and Central Bank of Sri Lanka. A panel mixed effect linear model for financial leverage were estimated. The positive sign of sales indicates that larger companies have higher debt ratios. This is consistent with a trade-off theory. Negative sign of return on assets supports the pecking-order hypothesis that firm with higher profitability has bigger capacity of internal financing. The negative sign of retained earnings supports market timing theory that managers try to time markets, issuing equity when their stock is overvalued. The negative sign of risk variable indicates that higher earnings volatility increases the possibility of a default and consequently increases distress costs. This in turn should reduce the leverage ratios. Gross Domestic Production with negative sign implies that growing economy gives confidence to the investors to invest more and reduce the leverage ratios of the firms
Keywords: Food and Beverage Companies; Financial Leverage; Panel Mixed Effect Linear Model